Large Scale Laboratory Direct Shear Tests on Ice - Roggensack, W. D. (Canadian Geotechnical Journal, 1975)
This paper presents the results of a series of large scale direct shear tests performed on lake ice. Test specimens were oriented with the principal stresses acting in the plane of the ice sheet, approximately normal to the long axes of the columnar crystals. Sample dimensions were large in comparison with mean crystal diameter, reducing the possibility of deviations introduced by size effects. Although a number of assumptions are made concerning stress conditions at failure, results for uniform, artificially ‘seeded’ test pond ice indicate a failure mechanism that is frictional and consistent with triaxial test data reported elsewhere. Post-peak shear resulted in the formation of a distinct failure zone that also displayed a frictional response. The direct shear test described is robust and simple, does not require elaborate sample preparation, and may present an alternative method of strength determination for ice mechanics problems where the shear box configuration duplicates field stress conditions and constraints.